A pilot study of cdc6 as a biomarker for circulating tumor cells in patients with lung cancer. Issue 6 (6th April 2020) - An, Cheng; Liu, Guijian; Cheng, Shi; Pang, Bo; Sun, Shipeng; Zhang, Yaying; Pan, Zhongdai; Kang, Xixiong
Abstract: Background: Cell division cycle 6 (cdc6) is a key factor of DNA replication initiation license system and a proto‐oncogene. It has been detected in some tumor tissues to aid cancer diagnosis in many research projects. However, it remains unclear that if cdc6 could be detected in the peripheral blood, just like liquid biopsy, in solid tumor patients. The aim of this study is to investigate the possibility of cdc6 as a biomarker for circulating tumor cells in patients with lung cancer. Methods: We first detected the expression of cdc6 in peripheral blood mononuclear cells (PBMCs) and tumor cells by in situ hybridization with cdc6 RNA probe. Then, we examined the expression of cdc6 in PBMCs from health individual, mononuclear cells from cord blood, or A549 cell line by RT‐qPCR. Furthermore, we used RT‐qPCR to test the cdc6 expression in PBMCs from tumor patients (test group) and non‐tumor individuals as a control group. Chi‐square test with Fisher's exact test was used to analyze the statistical significance of the difference. P  < .05 is considered as statistically significant difference. Results: When compared the cdc6 expression in cells from difference sources, we found that A549 tumor cell line had the strongest expression of cdc6, samples from cord blood showed the least expression level, indicating the detection strategy of RT‐qPCR is reasonable. Using this method, we studied whether cdc6 in Peripheral blood could be detected as a biomarker by examining cdc6 expression from PBMCs of patients with lung cancer. We found 20% of patients with lung cancer were cdc6 positive in PBMCs, whereas only 4.26% was found positive in the control group ( P  = .039, P  < .05). Conclusion: Cell division cycle 6 has a potential to be used as a circulating tumor cell biomarker for lung cancer. Further study in clinical application is still broad needed.